Brigham Young, pioneer prophet - Turner, John G. (Cambridge, Massachusetts ; London, England : The Belknap Press of Harvard University Press, 2012)
Provides a fully realized portrait of Mormon leader Brigham Young, a colossal figure in American religion, politics, and westward expansion.
A new creature -- The tongues of angels -- Acts of the apostles -- New and Everlasting Covenant -- Prophets and pretenders -- Word and will -- A new era of things -- One family -- Go ahead -- The whirlwind -- Let him alone -- The monster in the vale -- The soul and mainspring of the West.
Includes bibliographical references (p. 415-486) and index.
Description based on print version record.
Keywords: Young, Brigham, -- 1801-1877.; Church of Jesus Christ of Latter-day Saints -- Presidents -- Biography; Mormon Church -- Presidents -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Church of Jesus Christ of Latter-day Saints (Mormon); Electronic books